SUSTAINABLE DEVELOPMENT: THE ROLE OF GOVERNMENT IN ADDRESSING CLIMATE CHANGE - Abdul Halil Hi Ibrahim (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2023)
Sustainable development and climate change are two interconnected global issues that demand urgent attention and action. Governments play a central role in navigating these challenges by formulating and implementing effective policies and organizing adequate international frameworks. These policies include initiatives to reduce greenhouse gas emissions, promote the use of renewable energy, and improve the efficient use of natural resources. Through the imposition of policy instruments such as carbon taxes, green energy subsidies, and energy efficiency provisions, the government provides incentives for people and industries to transition to environmentally friendly operating models. In addition, government efforts also include building community resilience to the negative impacts of climate change with adaptation, mitigation, and disaster risk reduction-based approaches. Public education and environmental awareness are recognized as essential factors that encourage citizen participation and responsibility for the environment. In the international arena, cooperation between countries through global conferences and agreements such as the Paris Agreement is an important step to equalize perceptions and share global responsibilities.